PERIPHERAL OSSIFYING FIBROMA OF ORAL CAVITY: HISTOPATHOLOGIC DIFFERENTIAL DIAGNOSES - Shamim, Thorakkal (Journal of Ayub Medical College Abbottabad, 2012)
Peripheral ossifying fibroma is a benign neoplasm that usually develops from gingiva, presenting as an exophytic smooth surfaced pink or red nodular mass that is sessile or is less frequently seen on a pedicle. From the Indian perspective, it is usually noticed in 5th-6th decades of life with female predilection. Microscopically, the tumour shows stratified squamous epithelium and highly cellular fibrous stroma, sparse endothelial proliferation with fibroblasts and dystrophic calcifications. It has to be differentiated histopathologically from pyogenic granuloma, fibroma, peripheral giant cell granuloma, peripheral odontogenic fibroma and fibrous hyperplasia. A case of peripheral ossifying fibroma of maxillary gingiva in a 55-year-old Indian woman is reported. Keywords: Peripheral ossifying fibroma, oral cavity, gingival growth, histopathologic differential diagnosis